Mahaffie Stagecoach and Farm, Johnson County - Brockman, Timothy Lee (Kansas State University, The Chapman Center for Rural Studies, 2012)
The Mahaffie Stagecoach and farm was founded by Mr. and Mrs. Mahaffie, in the year 1858. Upon arrival to Kansas from Indiana, the family established their carrying trade business in Olathe, Kansas, located in Johnson County. Throughout the paper, different techniques of maps, photographs of the actual stagecoach site, periodicals, and censuses are used in order to discover what this historical community’s purpose was.
Timothy Lee Brockman, “Mahaffie Stagecoach and Farm, Johnson County,” Chapman Center Research Collections, accessed October 26, 2020, https://ccrsresearchcollections.omeka.net/items/show/102.
Keywords: Beatty Mahaffie; Fort Scott/Fort Leavenworth Trail; Johnson County; Lucinda Mahaffie; Mahaffie Stagecoach and Farm; Santa Fe Trail